Are Adolescents With High Mental Toughness Levels More Resilient Against Stress?. (3rd September 2012) - Gerber, Markus; Kalak, Nadeem; Lemola, Sakari; Clough, Peter J.; Perry, John L.; Pühse, Uwe; Elliot, Catherine; Holsboer‐Trachsler, Edith; Brand, Serge
Abstract Mental toughness has been explored predominantly within sport contexts. Nevertheless, it is difficult to conceive mental toughness as only applicable to athletes. This study examines whether mentally tough participants exhibit resilience against stress. This is a cross‐sectional study based on two different samples: Sample 1 consisted of 284 high school students (99 males, 185 females, M = 18.3 years). Sample 2 consisted of 140 first through fifth semester undergraduate students (53 males, 87 females, M = 20.0 years). Participants provided information about their level of perceived stress (10‐item Perceived Stress Scale), mental toughness (48‐item Mental Toughness Questionnaire) and depressive symptoms (Beck Depression Inventory). Consistent across the two samples, mental toughness mitigated the relationship between high stress and depressive symptoms. The interaction between stress and mental toughness explained 2% of variance in the adolescent sample and 10% of variance among young adults. The promotion of protective factors that foster resilient adaptation is a relevant issue. Mental toughness may appeal to individuals that are typically difficult to be reached with health interventions. Because mental toughness is part of young people's daily speech, it may serve as a less academic resource than other health psychology concepts. Copyright © 2012 John Wiley & Sons, Ltd.